2009
DOI: 10.1111/j.1365-2915.2009.00795.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative population dynamics of the bug Mepraia spinolai, a sylvatic vector of Chagas’ disease, in different hosts

Abstract: The aim of this work was to determine the impact of specific hosts on a population of Mepraia spinolai (Porter) (Hemiptera, Reduviidae), a sylvatic vector of Chagas' disease in Chile. We assessed whether a recently introduced host could be an important epidemiological factor in maintaining Chagas' disease in Chile. The study stressed the variations in survival, individual weight and fecundity in the insect population when the vector was raised with a species-specific food supply. The study compared the Europea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…This suggestion is supported by two facts: (i) rabbit burrows frequently occur next to M. spinolai colonies 18 , and (ii) rabbits have mostly nocturnal habits while M. spinolai is a predominantly diurnal species, therefore, facilitating feeding activity on resting rabbits 20 . Furthermore, when fed separately on different mammal species under laboratory conditions, kissing bugs reach the highest fecundity when fed on rabbits 31 . Our result stresses the importance of the alien European rabbit, described as a plague in the Mediterranean-type ecosystem of South American 20 , as a critical feeding resource for kissing bug populations 32 .…”
Section: Discussionmentioning
confidence: 97%
“…This suggestion is supported by two facts: (i) rabbit burrows frequently occur next to M. spinolai colonies 18 , and (ii) rabbits have mostly nocturnal habits while M. spinolai is a predominantly diurnal species, therefore, facilitating feeding activity on resting rabbits 20 . Furthermore, when fed separately on different mammal species under laboratory conditions, kissing bugs reach the highest fecundity when fed on rabbits 31 . Our result stresses the importance of the alien European rabbit, described as a plague in the Mediterranean-type ecosystem of South American 20 , as a critical feeding resource for kissing bug populations 32 .…”
Section: Discussionmentioning
confidence: 97%
“…Huang and Chi (2012), Huang et al (2018) and Chi et al (2020) discussed the problems of the ignorance of stage differentiation and male populations. Acuña‐Retamar et al (2009) reported that M. spinolai could survive starvation for more than 2 months. In this study, the female mean longevity was longer than 470 days, while the male mean longevity was longer than 500 days.…”
Section: Discussionmentioning
confidence: 99%
“…Food quality, including relative proportions of blood cells and plasma, may influence insect biology and affect bug colonies. Low blood viscosity will support a shorter period of bloodsucking, which may fail to elicit a behavioural response by the host [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, laboratory rearing of bed bugs is particularly important in understanding their vectorial role and in studying the association between natural conditions and laboratory situations for further experiments. Previous studies have demonstrated the adaptability of bugs to a wide range of environmental factors [ 2 ]. Laboratory colonies should experimentally reproduce the natural living conditions of bugs in a controlled environment to obtain consistent results in scientific research.…”
Section: Introductionmentioning
confidence: 99%